Synthesis and Physicochemical Properties of Hydrazides of Malonic Acid with Different Substitutes - T.V. Ghochikyan; A.I. Martiryan; G.A. Shahinyan; M.A. Samvelyan; A.S. Galstyan; H․R. Sargsyan; H․H. Ghazoyan (Eurasian Chemico-Technological Journal)
Shown that the rout of reaction of 2-ethoxycarbonyl-4,4-disubstituted-4-butanolide with hydrazine hydrate at soft conditions (45─50 ᵒC) strongly depends on the substituents on position 2 of butanolide cycle. The effect of substituents on the mechanism of above-mentioned reaction and yields of products has been investigated. Obvious that, dihydrazides of substituted malonic acid are produced when R3=H, whereas in the case of alkyl substituted butanolides intramolecular cyclization of intermediate occurs at the same conditions and as a result 4,4-disubstituted pyrazolidine-3,5-diones are produced. We studied physicochemical properties including antioxidant activity of the prepared compounds. The UV-Vis absorption spectroscopic studies reveal the effect of substituents on both absorption wavelength and molar absorption coefficient. From the spectra the transition type was determined. From dynamic light scattering measurements the mean hydrodynamic diameters of synthesized molecules is also determined. The antioxidant activity of malonic acid derivatives is studied using competitive reaction between hydroxyl radicals and free radical target p-nitroso-N,N-dimethylaniline. The rate constant between derivatives of malonic acid and hydroxyl radicals was determined and the results were compared with those of vitamin C.